Illuminating the molecular basis of human daylight vision - Sarah L. Schmidt; Jakub Dostal; Saumik Sen; Andrej Hovan; Deborah Walter; Martin V. Appleby; Asato Kojima; Hideaki E. Kato; John H. Beale; Miroslav Kloz; Gebhard F. X. Schertler; Polina Isaikina (Science, 2026)
Photopic vision, including fast motion and color perception in daylight, is mediated by cone opsins, specialized G protein–coupled receptors (GPCRs). Despite sharing the same chromophore, the three receptor subtypes absorb light at different wavelengths of the visible spectrum. The molecular mechanisms governing their spectral properties and exceptionally rapid responses remain largely unknown. We report cryo–electron microscopy structures of the human blue-sensitive (OPN1SW) and green-sensitive (OPN1MW) cone opsins in their dark-adapted states, combined with femtosecond-resolution spectroscopy, functional assays, and advanced simulations. The data reveal distinct chromophore stabilization mechanisms across human visual opsins and specific sequence adaptations in the GPCR microswitch motifs, underlining their structural plasticity and distinct activation mechanisms. These findings delineate the molecular basis of the evolutionary refinements fulfilling the needs of vision in daylight.